Analysis of Paris Agreement pledges informs UNFCCC negotiations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
To highlight the presence of agriculture in the Intended Nationally Determined Contributions (INDCs) ahead of the Conference of the Parties (COP) in Paris in December 2015, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and several partners systematically reviewed the 160 INDCs submitted by the parties to the United Nations Framework Convention on Climate Change (UNFCCC). The analysis demonstrated a country-driven demand for mitigation of agricultural emissions for non-annex 1 countries. UNFCCC country negotiators, donors, and climate finance investors used this and subsequent analyses to argue that agriculture is a critical sector to address in climate policy and should be prioritized in climate finance.